Codifying Waqf Fiqh in Indonesia: Historical Transformation and Legal Challenges in a Plural Legal System - MA Zaim; M Amanullah; Muhammad Abu Dzar (AL-FALAH : Journal of Islamic Economics, 2026)
Purpose: This article aims to examine the historical transformation and codification of waqf jurisprudence in Indonesia and to analyze the legal challenges arising in its implementation within a plural legal system. This study seeks to explain how Islamic law, state law, and customary law interact and negotiate in shaping national waqf regulations. Design/Method/Approach: This study employs a qualitative juridical-normative approach combined with historical analysis. Based on the theoretical framework of taqnīn al-fiqh (codification of Islamic law) and the theory of legal pluralism, the research analyzes legislation, classical fiqh texts, and relevant academic literature. Data is examined using content analysis and historical-critical analysis methods. Findings: Research indicates that the codification of waqf in Indonesia has developed gradually, beginning with pre-colonial religious practices, continuing through colonial administrative interventions, and culminating in the enactment of Law Number 41 of 2004 on Waqf. The plural legal system has significantly influenced the substance and direction of waqf codification through processes of negotiation and normative compromise. Nevertheless, its implementation still faces normative, institutional, and socio-cultural challenges. Originality/Values: This research contributes to the development of contemporary Islamic legal theory by demonstrating the dynamic and negotiative relationship between Islamic law and the modern state within the context of plural law. The study fills a gap in waqf studies by positioning codification as a historical-juridical process, rather than merely a normative or regulatory phenomenon, while also offering policy implications for strengthening waqf governance within a plural legal system.